2017
DOI: 10.4103/npmj.npmj_48_17
|View full text |Cite
|
Sign up to set email alerts
|

Variable presentation of retrocaval ureter: Report of four cases and review of literature

Abstract: Retrocaval ureter is a rare anomaly in which the ureter passes behind the inferior vena cava due to abnormal embryogenesis. Very few cases have been reported from Africa. Although the anomaly is congenital, patients become symptomatic in the third or fourth decade of life. We reviewed the records of four patients with the diagnosis of retrocaval ureter and managed in our centre between January 2010 and December 2016. Three patients presented with recurrent colicky right flank pain while one was asymptomatic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 9 publications
0
16
0
17
Order By: Relevance
“…A little over 200 cases have been reported worldwide since Hochstetter's first report in 1893 [3]. There are very few reported cases from Sub-Saharan Africa but Ahmed et al who managed four patients between 2010 and 2017 in Nigeria believe that the condition is probably under-reported [6]. In Ghana, Kyei et al reported on two patients with retrocaval ureter in 2011 [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A little over 200 cases have been reported worldwide since Hochstetter's first report in 1893 [3]. There are very few reported cases from Sub-Saharan Africa but Ahmed et al who managed four patients between 2010 and 2017 in Nigeria believe that the condition is probably under-reported [6]. In Ghana, Kyei et al reported on two patients with retrocaval ureter in 2011 [7].…”
Section: Discussionmentioning
confidence: 99%
“…This rare anomaly, first described in 1893 by Hochstetter in a cadaver [3] and the first clinical diagnosis in 1940 by Harrill [4], has an incidence of 0.06–0.17% worldwide [5]. Very few cases have been reported from Sub-Saharan Africa including four from Nigeria and two from Ghana [6, 7]. Though it no longer attracts the curiosity witnessed in the 1940s, it is still worth reporting on it especially in the case of successful surgical correction.…”
Section: Introductionmentioning
confidence: 99%
“…Introdução O ureter retrocava é uma malformação congênita rara, descrita pela primeira vez em 1893 por Hotchstetter (1) e caracterizada pela passagem do ureter posterior e medialmente a veia cava inferior. Ocorre mais comumente em homens do que em mulheres, numa proporção de cerca de 3-4:1, com incidência de 1 a cada 1500 em autópsias (2) .…”
Section: Abstract: Retrocaval Ureter Hydronephrosis Ureterothiasis Urogenital Abnormalities Laparoscopyunclassified
“…patients with mild hydronephrosis can be followed without surgery until it becomes symptomatic or increase in the degree of hydronephrosis 7 . Yen et al reported in their study that patients without symptoms and good excretory function on renogram can be followed with watchfull waiting 8 .…”
Section: Asymptomaticmentioning
confidence: 99%